Perlindungan Sosial Bagi Perempuan Disabilitas (Studi di Himpunan Wanita Disabilitas Indonesia (HWDI) Maluku) - Rahakbauw, Nancy; Salakory, David Marthen (ARISTO, 2018)
Social protection is a means of important to relieve the impact of poverty and afflictions faced by vulnerable groups such as women .It cannot be denied that women were treated in a discriminatory manner and has gotten the stigma in specific conditions. Women often victims, both with the sacred printing domestic and public domain, this condition more complicated again, if the woman has with disability. Limited and inability as a female either physically and psychologically cause women with disability not able to meet a need maximally. Research aims to understand social protection forms received and constraints experienced by women with disability in get access to range of services available or provided by the government. Research will be implemented in an institution the set of women with disability Indonesia (HWDI) Kota Ambon, Provinsi Maluku .This research used the qualitative method which describes about the forms of social protection as well as constraints experienced by the Women Disability. The object of this research is focused on the members of the HWDI organization. Results of the research show that the received protection form, though Women Disability is social insurance, social assistance and Social Empowerment and obstacles faced in accessing services is uneven dissemination of information as well as physical limitations and treatment diskirminasi of the community and the public is not aksesibiti for persons with Disability.